A probabilistic and statistical approach as a means of predicting the efficiency of hydraulic fracturing - Gabdrakhmanova, Clara; Usmanova, Flyura; Khramov, Gennady (Eastern-European Journal of Enterprise Technologies, 2016)
The study considers mathematical data on the efficiency of using a single-stage and multistage types of hydraulic fracturing for petroleum field development. The research is based on the geological and physical characteristics of the deposits in the latitudinal segment of the Ob River area, which has helped justify the method of choosing the HF technique. The probabilistic and statistical analysis of the commercial efficiency statistics has determined the quantitative criteria for selecting the crack parameters such as length, height and the amount of proppant injected, which can facilitate making estimates for the use of a single-stage and multistage types of hydraulic fracturing. The productive horizon AC-12-3 has a complex geological and physical structure and low reservoir properties, which greatly complicates its development but facilitates active formation of its hard-to-recover deposits. The study has revealed that the technology used to enhance oil recovery from the horizon BC-8-1 on the basis of a single-stage hydraulic fracturing can be effective for quite a limited time not exceeding 3-4 years. Meanwhile, the use of the multistage HF technology on the horizon AC-12-3 showed its higher efficiency compared to the single-stage HF technology. The results of the probabilistic and statistical analysis of the commercial application of the multistage hydraulic fracturing technology have proved that it is necessary to take into account the geological and physical peculiarities of a horizon in order to choose an appropriate technology of petroleum recovery.